Development of procedures for modifying the cipher GOST 28147 - Yevseiev, S. P.; Korolyov, Roman; Tkachov, Andrii; Nimchenko, Anastasia (Національний технічний університет "Харківський політехнічний інститут", 2021)
The entry of mankind into the era of high technologies, the rapid growth of computer technology contributes to the expansion of the range of electronic services. To ensure the security of confidential information, personal data, cryptographic systems of traditional cryptography (symmetric cryptosystems) and public key cryptography (asymmetric cryptosystems) are used. As a rule, the former provides security services, the latter provide key distribution. However, in the conditions of totalitarian surveillance in society by the special services of developed countries, cryptographic tabs are embedded in cryptographic algorithms, which, on the one hand, provide “quick” access for special services to confidential information, and on the other hand, allow intruders to break into the cryptosystem and obtain user data. The article proposes a modification of the well-known GOST 28147-89 algorithm, which ensures the "elimination" of possible crypto-bookmarks and an increase in crypto-resistance in the post-quantum period (the emergence of a full-scale quantum computer that allows hacking modern symmetric and asymmetric cryptosystems based on Grover and Shor algorithms). It is proposed to use the procedures for modifying the block-symmetric encryption algorithm (BSEA) GOST 28147-89 (2009, 2015) in OFB mode, which will make it possible to form a pseudo-random sequence based on dynamic changes in the S-box, and provide the required level of security.

Вступ людства в еру високих технологій, бурхливе зростання обчислювальної техніки сприяє розширенню спектра електронних послуг. Для забезпечення безпеки конфіденційної інформації, персональних даних використовуються криптографічні системи традиційної криптографії (симетричні криптосистеми) і криптографії з відкритим ключем (несиметричні криптосистеми). Як правило, перші забезпечують послуги безпеки, другі - розподіл ключів. Однак в умовах тоталітарної стеження в суспільстві з боку спец служб розвинених держав в криптографічних алгоритмах "вбудовуються" криптографічні закладки, які з одного боку забезпечують "швидкий" доступ спецслужб до конфіденційної інформації, з іншого боку дозволяють зловмисникам зламувати криптосистему і отримувати дані користувачів. У статті пропонується модифікація відомого алгоритму ГОСТ 28147-89, яка забезпечує "усунення" можливих криптозакладок і підвищення криптостійкості в умовах постквантового періоду (поява повномасштабного квантового комп'ютера, який дозволяє зламати на основі алгоритмів Гровера і Шора сучасні симетричні і несиметричні криптосистеми). Пропонується використовувати процедури модифікації блочно-симетричного алгоритму шифрування (БСШ) ГОСТ 28147-89 (2009, 2015) в режимі OFB, що дозволить формувати псевдовипадкову послідовність на основі динамічного зміни S-box, і забезпечити необхідний рівень стійкості.
Розробка процедур модифікації шифру ГОСТ 28147
Keywords: block-symmetric cipher; stream cipher; GOST 28147-89; DSTU 28147-2009; блочно-симетричний шифр; потоковий шифр; ГОСТ 28147-89; ДСТУ 28147-2009